2020
DOI: 10.1016/j.chb.2019.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating E-learning systems success: An empirical study

Abstract: Please refer to published version for the most recent bibliographic citation information. If a published version is known of, the repository item page linked to above, will contain details on accessing it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

93
770
17
89

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 818 publications
(969 citation statements)
references
References 130 publications
(154 reference statements)
93
770
17
89
Order By: Relevance
“…This field of science facilitates the provision of the facilities for designing new scientific environments, which was not possible in the past. Therefore, the evaluation of e-learning systems is vital to ensure successful implementation, effective use, and positive impacts on learners [31].…”
Section: Discussionmentioning
confidence: 99%
“…This field of science facilitates the provision of the facilities for designing new scientific environments, which was not possible in the past. Therefore, the evaluation of e-learning systems is vital to ensure successful implementation, effective use, and positive impacts on learners [31].…”
Section: Discussionmentioning
confidence: 99%
“…Among them, many have critically examined the dimensions and CSFs of the E-Learning system. Some studies [5], [14,36] have classified the CSFs of E-Learning into different dimensions such as Institutional Management Service, Instructors, System and Technological, Students, and Content Design. In the first stage of this study, all possible success factors related to E-Learning were identified which resulted in 36 CSFs.…”
Section: Framework For the Identification Of Csfs In E-learningmentioning
confidence: 99%
“…Students are considered as one of the main stakeholders of the E-Learning system. It has been observed that students are given preference over the other stakeholders as they are the main beneficiary of the E-Learning system [5,37,38]. Moreover, students are expected to acquire assistance from the system and the system would be more successful and valuable if students use it appropriately.…”
Section: Students' Dimensionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the adoption of TAM, the critical factors for the acceptance of E-learning had been identified by several researchers [24,[54][55][56][57][58][59][60][61][62]. Regarding this study, the goal was to analyze the E-learning acceptance behavior of the UAE University students, through whom, better understandings of implications to implement E-learning systems in UAE universities successfully could be gained.…”
Section: Determinants Of Students' Acceptance Of E-learning"mentioning
confidence: 99%